(3cTa GdbfGY Yf GdSQ GdecJhes - (3eMeO cGXe GdWhSj GdNQGSGfj,J (B1329 (3g` s
(3ChdgG (B:s
(3hHYO agPg aQGFO LdjdI cGdOQ GdefXhe haQGFO LejdI JcTa GdbfGY Yf GdSQ GdecJhe s
(3BNQgG (B:s
(3cPdc de jcf JYOO GdYfhGf chf MQcI hMOg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B11s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs